Imaging of Müller-Weiss Disease - Carrascoso, Javier; Monteagudo, Manuel; Llopis, Eva; Jiménez, Mar; Recio, Manuel; Maceira, Ernesto (Seminars in Musculoskeletal Radiology, 2023)
Müller-Weiss disease (MWD) is the result of a dysplasia of the tarsal navicular bone. Over the adult years, the dysplastic bone leads to the development of an asymmetric talonavicular arthritis with the talar head shifting laterally and plantarly, thus driving the subtalar joint into varus. From a diagnostic point of view, the condition may be difficult to differentiate from an avascular necrosis or even a stress fracture of the navicular, but fragmentation is the result of a mechanical impairment rather than a biological dysfunction.Standardized weight-bearing radiographs (anteroposterior and lateral views) of both feet are usually enough to diagnose MWD. Other imaging modalities such as multi-detector computed tomography and magnetic resonance imaging in early cases for the differential diagnosis can add additional details on the amount of cartilage affected, bone stock, fragmentation, and associated soft tissue injuries. Failure to identify patients with paradoxical flatfeet varus may lead to an incorrect diagnosis and management. Conservative treatment with the use of rigid insoles is effective in most patients. A calcaneal osteotomy seems to be a satisfactory treatment for patients who fail to respond to conservative measures and a good alternative to the different types of peri-navicular fusions. Weight-bearing radiographs are also useful to identify postoperative changes.
Keywords: Müller-Weiss disease; tarsal navicular; avascular necrosis; varus hindfoot; dysplasia